Energy harvesting for IOT - Phua, Jing Tian (2017)
This project aims to improve the sustainability of Internet of Things through recycling light energy used in indoor environments. It consist of an indoor solar-powered, Open- Source Microcontroller with In-Built WiFi functions, powering a Humidity and Temperature sensor, designed to transmit collected data to a nearby database or monitoring device for environmental tracking of an indoor air-conditioned room. The experiments of this project would prove that harvesting indoor energy and deploying a self-sustainable IoT network is possible and viable for wide industrial applications. Experiments are conducted under standard testing conditions to simulate an actual indoor environment and the energy consumption of the setup is measured while operating under a deploy-and-forget mode. Data collected are recorded in a cloud server through an Application Programming Interface, Thingspeak. The circuit design consist of an array Amorphous Silicon Solar Cells, a set of ‘AA’ Nickel Metal Hydride Batteries, a DC-DC Buck Converter, a Humidity and Temperature sensor and a newly launched IoT-specific Microcontroller board called Arduino MKR1000. The Microcontroller possess impressive communication capabilities while consuming very low power as compared to many commercial products in the market. In addition, different types of Solar Cells and Battery Storages are accessed through IV Curve performance parameters and power generation capabilities to select the best performing and sustainable option under indoor conditions. Implementations and results for this project will be included to display the effectiveness, reliability and sustainability of this IoT sensor circuit as compared to existing technologies and projects within the industry.